Total VFA value, NH3 and Invitro Digestibility of Cabbage and Mustard Vegetable Waste Distilled with Various Carbohydrate Sources: Nilai VFA Total, NH3 dan Kecernaan Invitro Limbah Sayur Kol dan Sawi yang Disilase dengan Berbagai Sumber Karbohidrat - Adelina, Triani; Saleh, Eniza; Anwar Efendi Harahap; Hidayat, Muhammad Ridwan (Buletin Peternakan Tropis, 2024)
Market vegetable waste produced in Pekanbaru City can be produced up to 235.45 tons/day, this has the potential to utilize market waste in the form of cabbage and mustard greens which are used as feed. This research aims to produce NH3 production values, VFA and dry matter digestibility (DMD), organic matter digestibility (OMD) of vegetable waste silage with the addition of various carbohydrate sources. The research method was carried out experimentally using a Completely Randomized Design (CRD) pattern of 4 treatments and 5 replications. Treatments are P1 = vegetable waste silage + 30% rice bran; P2= vegetable waste silage + 30% corn flour; P3%= vegetable waste silage + 30% addition of piles; and P4 = vegetable waste silage + addition of 10% rice bran + 10% corn flour + 10% waste. The parameters observed were dry matter digestibility, organic matter digestibility, NH3 production and total VFA. The research results showed that the addition of various carbohydrate sources had no significant effect on silage NH3 (P>0.05), but had a very significant difference (P<0.01) on the DMD, OMD and total VFA values. The addition of various carbohydrate sources is able to increase the In Vitro digestibility value and is able to maintain NH3 production. The addition of a carbohydrate source from corn flour resulted in superior DMD, DMO and total VFA values compared to other treatments